The immunomodulatory function of adenosine in sepsis - Zhang, Teng; Yu-Jing, Li; Ma, Tao (Frontiers in Immunology, 2022)
Sepsis is an unsolved clinical condition with a substantial mortality rate in the hospital. Despite decades of research, no effective treatments for sepsis exists. The role of adenosine in the pathogenesis of sepsis is discussed in this paper. Adenosine is an essential endogenous molecule that activates the A1, A2a, A2b, and A3 adenosine receptors to regulate tissue function. These receptors are found on a wide range of immune cells and bind adenosine, which helps to control the immune response to inflammation. The adenosine receptors have many regulatory activities that determine the onset and progression of the disease, which have been discovered via the use of animal models. A greater understanding of the role of adenosine in modulating the immune system has sparked hope that an adenosine receptor-targeted treatment may be used one day to treat sepsis.